STATE ROLE AND FORMS OF STATE SUPPORT DEVELOPMENT OF SMALL AND REGIONAL AVIATION IN THE RUSSIAN FEDERATION - R. R. Nizametdinov (Научный вестник МГТУ ГА, 2016)
In article considered subsidy mechanisms of small and regional aviation in the Russian Federation.